Interactions Between a Large Marine Protected Area, Pelagic Tuna and Associated Fisheries - Curnick, David J.; Collen, Ben; Koldewey, Heather J.; Jones, Kate E.; Kemp, Kirsty M.; Ferretti, Francesco (Frontiers in Marine Science, 2020)
The efficacy of large marine protected areas (MPA) for the conservation of mobile pelagic species is widely debated. Here, we quantified spatial and temporal trends in standardised catch per unit effort (CPUE) of two target pelagic species, yellowfin (Thunnus albacares) and bigeye tuna (Thunnus obesus) in the Indian Ocean to analyse the impact of the British Indian Ocean Territory (BIOT) MPA’s creation in 2010. We applied generalised additive mixed effects models to historical BIOT longline fishery logbooks and official catch and effort statistics from the Indian Ocean Tuna Commission (IOTC) to standardise CPUEs and to evaluate long-term trends and distribution patterns across the equatorial Indian Ocean. We find that trends in population indices from within BIOT prior to the MPA’s establishment mirror those of the wider Indian Ocean. We also suggest that there may be behavioural plasticity within the yellowfin tuna stock, with some individuals possibly undertaking alternative migration patterns or exhibiting residency behaviour within BIOT. Yet, we find no direct evidence of any improvement in standardised CPUE indices of either species in the area surrounding the BIOT MPA, eight years after its establishment. The average size of yellowfin and bigeye tunas caught both increased after the MPA’s establishment. These patterns were also evident across the equatorial Indian Ocean, suggesting that any MPA effect is in combination with other regional drivers, such as behavioural changes in the fishing fleets in response to the threat of Somali Piracy. We therefore conclude that BIOT MPA may be providing local conservation value to tunas, but it is not significant enough to halt the overall regional decline in yellowfin tuna stocks. Thus, we emphasise that large MPAs should be considered in conjunction with other fishery management regulations and wider regional processes, rather than as a silver bullet, in order to provide the conservation and management benefits needed for mobile species like tunas.